Study Room Online Reservation in UUM Library - Salah, Razwan Mohmed (2009)
This study introduces the online room reservation system that is developed to facilitate the development of shared virtual environments. The main objective of this project is to assist the students in gaining an easier and faster way of reservation, providing them with more selections, and real time information. The library will be able to offer students the precise estimation of rooms schedule in the service management. This system is to be implemented by integrating online technology with web services.